Propensity score‐matched study of laparoscopic and open surgery for colorectal cancer in rural hospitals. Issue 10 (October 2016) - Nakao, Toshihiro; Shimada, Mitsuo; Yoshikawa, Kozo; Higashijima, Jun; Tokunaga, Takuya; Nishi, Masaaki; Takasu, Chie; Kashihara, Hideya; Suzuka, Ichio; Nishizaki, Takashi; Okitsu, Hiroshi; Yagi, Toshiyuki; et al.
Abstract: Background and Aim: Various randomized clinical studies have suggested that short‐ and long‐term outcomes of laparoscopic surgery (LAP) for colorectal cancer are comparable with those of open surgery (OP). However, these studies were performed in high‐volume hospitals. The aim of the present study was to compare the outcomes of LAP versus OP for colorectal cancer in rural hospitals. Methods: This was a multicenter retrospective propensity score‐matched case–control study of patients who underwent colorectal surgery from January 2004 to April 2009 in 10 hospitals in Japan. All patients underwent curative surgery for pathologically diagnosed stage II or III colorectal cancer. The primary end point was 5‐year overall survival (OS). The secondary end points were disease‐free survival (DFS) and postoperative complications. Results: In total, 319 patients who underwent LAP and 1020 patients who underwent OP were balanced to 261 pairs. There was no significant difference in the OS and DFS between two groups. The operation time was significantly shorter for OP than for LAP. Blood loss was significantly lower in LAP than in OP. There was no difference in intraoperative morbidity between the two groups. The postoperative morbidity was significantly lower in LAP than in OP. The hospital stay was significantly shorter in LAP than in OP. There was no significant difference in 90‐day postoperative mortality. Conclusions: Laparoscopic surgery may be a feasible option for colorectal cancer in rural hospitals.